Development Of "SEHATI" Application To Improve Adolescent's Understanding Of Reproductive Health - Kumalasari, Intan; Jaya, Herawati (Journal of Applied Nursing and Health, 2024)
Background: Adolescent Reproductive Health (KRR) is a government program in Indonesia that has been implemented since 2000. The aim is to ensure that the young generation is healthy and prosperous. Teenagers are still looking for answers to reproductive health problems themselves, consulting friends, social media and other online sources because they do not fully understand the material offered in this program. Adolescents may be more likely to participate in risky behavior, such as engaging in sexual intercourse at a younger age, due to the ease of obtaining information. Methods: The "SEHATI" app, developed as a result of this research, will teach teenagers more about reproductive health. By using the ADDIE methodology (analysis, design, development, implementation and evaluation), this research adheres to a Research and Development approach. Results: Media experts gave a product validation score of 75%, material experts gave a score of 100%, and educational practitioners gave a score of 99.5%, all of which indicate that the product is very suitable for use. Scores of 77.3% and 88% were achieved in small-group trials and large-group trials, respectively. This shows how well the product works. As many as 89% of students gave positive answers throughout the evaluation stage. Conclusion: With an 80% increase in student understanding, this app has great potential for future improvements in terms of content, realism, language, presentation, graphics and student learning motivation with the hope of becoming a resource for the younger generation to learn more about reproductive health.